Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan dan Hasil Belajar Siswa pada Materi Sistem Pencernaan Manusia di Kelas XI IPA 2 SMAN 1 Bandar Petalangan - Nadra, Syarifah (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This study aimed to enhance students' interest and learning outcomes in this subject using discussion method and Problem Blended Learning (PBL) model. The research, conducted to determine the most effective teaching method, employed Classroom Action Research with two cycles, including pre-cycle actions. Each cycle consisted of four stages: 1) planning, 2) implementation, 3) observation, and 4) reflection. Results revealed an improvement in learning motivation, as seen in students' active participation during question-and-answer sessions. In the 2020/2021 academic year, the first cycle showed 32.14% of students actively engaged, increasing to 60.71% in the second cycle. Regarding the on-time assignment submission indicator, participation rose from 71.42% in the first cycle to 96.42% in the second cycle. Additionally, the percentage of students scoring above the minimum passing grade increased from 46.43% in the first cycle to 71.42% in the second cycle.